Character Education Framework In Ethical Philosophy - Azkiya, Annisa Husna; Tuddairoh, Jauhariyah; Affandi, Akhmad (UNIVERSITAS PAKUAN, 2025)
Character education is a fundamental aspect of the educational system, aiming to shape individuals who are not only intellectually capable but also morally and spiritually mature. This study seeks to examine how ethical philosophy provides a conceptual foundation for the development of holistic and functional character education. Using a qualitative approach with a literature review method, this research explores the ethical thoughts of prominent figures such as Immanuel Kant, Aristotle, and Ibn Miskawayh in relation to character formation in students. The findings reveal that ethical philosophy offers a rational, normative, and reflective framework for understanding moral values, which are central to character education. Character is positioned as the result of internalizing values through continuous habituation and ethical reflection, rather than merely compliance with normative rules. The integration of three ethical approaches deontological, teleological, and virtue ethics within the educational system results in a learning structure that not only shapes good behavior but also fosters deep moral awareness. Therefore, character education grounded in ethical philosophy is considered capable of addressing contemporary educational challenges and forming individuals who are socially responsible and morally consistent.